Minimal standards for the description of new genera and species of rhizobia and agrobacteria. Issue 7 (29th May 2019) - de Lajudie, Philippe M.; Andrews, Mitchell; Ardley, Julie; Eardly, Bertrand; Jumas-Bilak, Estelle; Kuzmanović, Nemanja; Lassalle, Florent; Lindström, Kristina; Mhamdi, Ridha; Martínez-Romero, Esperanza; Moulin, Lionel; Mousavi, Seyed Abdollah; et al.
Abstract : Herein the members of the Subcommittee on Taxonomy of Rhizobia and Agrobacteria of the International Committee on Systematics of Prokaryotes review recent developments in rhizobial and agrobacterial taxonomy and propose updated minimal standards for the description of new species (and genera) in these groups. The essential requirements (minimal standards) for description of a new species are (1) a genome sequence of at least the proposed type strain and (2) evidence for differentiation from other species based on genome sequence comparisons. It is also recommended that (3) genetic variation within the species is documented with sequence data from several clearly different strains and (4) phenotypic features are described, and their variation documented with data from a relevant set of representative strains. Furthermore, it is encouraged that information is provided on (5) nodulation or pathogenicity phenotypes, as appropriate, with relevant gene sequences. These guidelines supplement the current rules of general bacterial taxonomy, which require (6) a name that conforms to the International Code of Nomenclature of Prokaryotes, (7) validation of the name by publication either directly in the International Journal of Systematic and Evolutionary Microbiology or in a validation list when published elsewhere, and (8) deposition of the type strain in two international culture collections in separate countries.